Midwives’ practice challenges in triaging expectant mothers: a qualitative study in Mpumalanga maternity units, South Africa - Ngwenya, Mxolisi Welcome; Muthelo, Livhuwani; Rasweswe, Melitah Molatelo; Mothiba, Tebogo Maria (Frontiers in Medicine, 2025)
BackgroundIn the early decades, triage systems were universally implemented in accident and emergency departments. However, in recent years, various maternity triage systems, including digital technology triage models, have been gradually employed to evaluate the urgency of arriving pregnant women in maternity units. These systems face practice challenges, especially in South Africa, where data on triaging practices in maternity units are scarce, particularly in Mpumalanga province. Hence, this study seeks to identify and describe the practice challenges influencing the triaging of expectant mothers by midwives working in the maternity units of Mpumalanga province.MethodsA qualitative, exploratory descriptive design underpinned this study. The maximum variation purposive sampling technique was used to select midwives working in the maternity units of Mpumalanga province. Semi-structured interviews were conducted for data collection, and data saturation was reached and confirmed with the 20th participant. Thematic analysis was employed for data analysis.ResultsThe study highlighted that the triaging of expectant mothers by midwives is plagued by numerous practice challenges. Among these challenges were a shortage of resources, poor infrastructure, and incompetence among midwives. Nonetheless, the most concerning practice challenge was poor leadership, evidenced by the midwives’ viewpoints that there is a lack of support, whether informational (triage policies/protocols) or psychological.ConclusionThese findings suggest a need to rethink healthcare service delivery priorities to enable a clinical environment that improves the provision of quality care. Therefore, urgent action is required to develop context-specific triage protocols and guidelines for maternity units in Mpumalanga province. Moreover, multifaceted support programs aimed at empowering midwives and fostering a blame-free, non-toxic environment should be designed and implemented. Addressing the identified challenges will not only improve the provision of care but will also enhance the patient experience.